"Stacked-arene"-type organocatalysts: Utilization of π-π interaction as an electron tuning tool. (6th July 2022) - Yamamoto, Yuki; Inoue, Aiko; Sakai, Dan; Otawa, Yuna; Mori, Keiji
Graphical abstract: Abstract: We have developed a novel type of organocatalyst having a 1, 8‑diarylnaphthalene core, namely, a "Stacked-arene"-type organocatalyst. The key point of the catalyst design is the π-π interaction based electron tuning. This through space electron tuning effect is effective enough for the improvement of the catalytic activity (reducing the catalyst loading), and this tendency was evaluated by the Michael addition reaction between nitrostyrene and dimethyl malonate. Additional experiments suggest that the expected improvement of the hydrogen bonding ability plays a critical role in the high performance of the designed catalyst.